ANALISIS MODEL SUPPLY PADA JARINGAN SISTEM KELISTRIKAN DI FAKULTAS TEKNIK UNIVERSITAS UDAYANA BUKIT JIMBARAN - Yuniari, Margareta; Giriantari, Ida Ayu Dwi; Sukerayasa, I Wayan (Jurnal Teknologi Elektro, 2017)
The addition of the power source to the main network is one way to improve the quality of electric power system, network reliability and to reduce power losses . The addition of the energy source is a smart microgrid system. The smart microgrid technology is a technology that uses renewable energy as a main supply. Smart microgrid system consists of a 24 kWp solar power, Wind Turbine 5 kWp system 240 kVAh battery and genset 20 kVA. The smart microgrid system to be implemented at the Engineering Faculty of Udayana University. The results showed the power loss (losses) on the electrical grid at FT Bukit Jimbaran before the advent of smart microgrid system to the network, acquired losses of 6.4 kW or 3.68% of the total load when the network is supplied from PLN and after the inclusion of smart microgrid system and generator sets to the grid obtained by losses of 1.2 kW or decreased losses of 0.69% of the total expenses of 173.54163 kW. Reliability indices obtained at the Technical University of Udayana network after the entry smart microgrid system when interconnected with PLN namely SAIFI: 0.1029, SAIDI: 1.9229 hours / customer, and CAIDI: 18.686 hours / interruption.
Keywords: Smart microgrid system, PLTS, Wind Turbin, generator set, losses, keandalan